Shear Bond Strength of Ceramic Brackets to Ceramic Surfaces Using No-primer Adhesive - Tariverdi, Navid; Bayatian, Amir; Tarzi, Pedram; Shahmari, Zahra; Mirmohammadsadeghi, Hoori (Journal of Dental School, 2025)
Objective(s): To simplify the bonding steps of orthodontic brackets, GC Ortho Connect adhesive with a primer solution in its composition has been presented. As a result, the primer application phase after etching has been eliminated. This study examined the shear bond strength (SBS) and adhesive remnant index (ARI) of ceramic brackets to the ceramic surfaces using two bonding systems, GC Ortho Connect and Brace Paste American Composite, in the presence or absence of silane. Methods: In this laboratory study, 40 IPS e.max ceramic blocks were assigned to four groups, and Protect ceramic brackets were bonded to them using GC Ortho Connect or Brace Paste American Composite adhesive in the presence or absence of silane (Primer Ceramic X Rely). Under a stereo microscope, the ARI was ascertained, and a universal testing machine assessed the SBS amounts. One-way ANOVA, Post hoc Tukey tests, and chi-squared test were used for statistical analysis, at a significance level of 0.05. Results: The SBS of ceramic brackets to porcelain using GC Ortho Connect without silane and Brace Paste American Composite with silane differed significantly (p=0.008), although other pair comparisons did not show significant differences. There was no discernible difference between the groups in terms of type of failure (p=0.84). Conclusion: It is acceptable to use Brace Paste American Composite adhesive with or without silane, or GC Ortho Connect adhesive with silane, to achieve the bond of ceramic brackets to porcelain surfaces. However, the bond strength between ceramic brackets and porcelain surfaces was inadequate when using GC Ortho Connect without silane.